2022
DOI: 10.3897/phytokeys.214.97612
|View full text |Cite
|
Sign up to set email alerts
|

Corrigendum: García N, Cuevas C, Sepúlveda JE, Cádiz-Véliz A, Román MJ (2022) Two new species of Miersia and their phylogenetic placements alongside the recently described M. putaendensis (Gilliesieae, Allioideae, Amaryllidaceae). PhytoKeys 211: 107–124. doi: 10.3897/phytokeys.211.87842

Abstract: According to Escobar (2012), there are two kinds of floral appendages around the staminal tube or urn in Miersia: 1) the upper pair of appendages are of staminal origin and 2) the four lateral appendages, one pair on each side of the staminal tube, are of tepaliferous origin. Consequently, mentions to “tepaliferous appendages” in diagnoses, descriptions, identification key and figure captions of our recent article (García et al. 2022) should be changed to “floral appendages”, to denote the mixed nature of thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Upon observing its morphological characteristics, such as its mealy, deciduous perennials, and overwintering through an above-ground mealy resting bud, along with bracts that are typically smaller and somewhat swollen or thick, calyx prominently 5-veined, corolla narrow tube and lobes apex deeply emarginate, we have identified this species as belonging to the Primula section Aleuritia. After consulting relevant literature (Smith and Word 1926;Smith and Fletcher 1944;Hu 1986Hu , 1990Fang 1994Fang , 2003Hu and Kelso 1996;Wu 1999;Richards 2003) and herbarium specimens (BM, E, K, KUN, and US), we have concluded that this species is indeed unique and previously undescribed, and similar to Primula rhodochroa W.W.Sm. and P. socialis F.H.Chen & C.M.Hu.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Upon observing its morphological characteristics, such as its mealy, deciduous perennials, and overwintering through an above-ground mealy resting bud, along with bracts that are typically smaller and somewhat swollen or thick, calyx prominently 5-veined, corolla narrow tube and lobes apex deeply emarginate, we have identified this species as belonging to the Primula section Aleuritia. After consulting relevant literature (Smith and Word 1926;Smith and Fletcher 1944;Hu 1986Hu , 1990Fang 1994Fang , 2003Hu and Kelso 1996;Wu 1999;Richards 2003) and herbarium specimens (BM, E, K, KUN, and US), we have concluded that this species is indeed unique and previously undescribed, and similar to Primula rhodochroa W.W.Sm. and P. socialis F.H.Chen & C.M.Hu.…”
Section: Introductionmentioning
confidence: 97%
“…The genus Primula L. is one of the largest genera in the Primulaceae with more than 500 species, and widely distributed in the temperate and alpine regions of the Northern Hemisphere with its major concentration in the Sino-Himalayan regions and in western China, with only a few occurring on mountains in Ethiopia, tropical Asia and South America (Hu 1990(Hu , 1994Hu and Kelso 1996;APG 2016). In China, more than 300 species of Primula have been recorded, which are concentrated in the southwestern and northwestern provinces, with only a few species distributed in other regions (Hu and Kelso 1996;Richards 2003). Sichuan Province is a particularly important biodiversity hotspot in China.…”
Section: Introductionmentioning
confidence: 99%
“…0.5 mm, fruit compressed, nutlets acute ovoid and disc narrowly ovate-triangular (Figs 1, 3). After conducting a comprehensive review of relevant literature (Gürke 1894;Brand 1931;Popov 1953;Vvedensky 1961;Sharashova 1962;Goloskokov 1964;Riedl 1967;Chukavina 1984;Nasir 1989;Zhu et al 1995;Ovczinnikova 2009) and examining specimens of Lappula from the Herbaria of Royal Botanic Garden Edinburgh (E), Muséum National d'Histoire Naturelle (P), Komarov Botanical Institute of RAS (LE), Moscow University (MW), Central Siberian Botanical Garden SB RAS (NS), Institute of Botany, Chinese Academy of Sciences (PE), North-western Institute of Botany (WUK), Northwest Institute of Plateau Biology, Chinese Academy of Sciences (HNWP), National Herbarium of Uzbekistan (TASH) and Xinjiang Institute of Ecology and Geography, Chinese Academy of Sciences (XJBI), we concluded that it did not match morphologically with any known species of Lappula. Based on these distinctive morphological features, we confirmed that it was a new species, which we describe and illustrate here as Lappula effusa D.H.Liu & W.J.Li.…”
Section: Introductionmentioning
confidence: 99%
“…0.5 mm, fruit compressed, nutlets acute ovoid and disc narrowly ovate-triangular (Figs 1, 3). After conducting a comprehensive review of relevant literature (Gürke 1894;Brand 1931;Popov 1953;Vvedensky 1961;Sharashova 1962;Goloskokov 1964;Riedl 1967;Chukavina 1984;Nasir 1989;Zhu et al 1995;Ovczinnikova 2009) and examining specimens of Lappula from the Herbaria of Royal Botanic Garden Edinburgh (E), Muséum National d'Histoire Naturelle (P), Komarov Botanical Institute of RAS (LE), Moscow University (MW), Central Siberian Botanical Garden SB RAS (NS), Institute of Botany, Chinese Academy of Sciences (PE), North-western Institute of Botany (WUK), Northwest Institute of Plateau Biology, Chinese Academy of Sciences (HNWP), National Herbarium of Uzbekistan (TASH) and Xinjiang Institute of Ecology and Geography, Chinese Academy of Sciences (XJBI), we concluded that it did not match morphologically with any known species of Lappula. Based on these distinctive morphological features, we confirmed that it was a new species, which we describe and illustrate here as Lappula effusa D.H.Liu & W.J.Li.…”
Section: Introductionmentioning
confidence: 99%